Leachability characteristic of heavy metals and associated health risk study in typical copper mining-impacted sediments. (January 2020) - Yan, Bo; Xu, Da-Mao; Chen, Tao; Yan, Zi-Ang; Li, Li-Li; Wang, Ming-Hui
Abstract: A total of 100 samples were collected from the sediments of a typical copper mining area, south China. Leaching concentrations of selected heavy metals (Ni, Cd, Cu, Pb, Zn, Ba, As, and Hg) were measured to evaluate their distribution patterns and associated health risk. Leaching concentrations of Cu (3.58 ± 1.49 mg/L), Pb (1.50 ± 1.06 mg/L), and Zn (4.04 ± 1.68 mg/L) were significantly higher than the other metals in the samples. By evaluating the spatial heterogeneity, it was found that leaching metal concentrations did not decrease with environmental gradients, mostly caused by diverse distribution in pollution sources. The hazard index and carcinogenic risk indices showed significant risks of human exposure. For public safety, priority governance should be given to the main pollutants (Cd, Cu, Pb, Zn, and As) in sediments. In future studies, the integrated data will be urgently required for local stakeholders to conduct environmental monitoring and remediation scenarios. Graphical abstract: Image 1 Highlights: Concentrations of heavy metals leaching from ten sediment layers were determined. Geographical and depth-distribution of leaching metal concentrations were studied. Sources of elemental enrichment in sediments were quantified using APCS-MLR model. Leaching metal exposure to studied sediments had posed serious public health risks.